Karl Polanyi on the Limitations of Formalism in Economics - Stanfield, James Ronald; Carroll, Michael C.; Wrenn, Mary V. (Choice in Economic Contexts, 2006)
This chapter examines Karl Polanyi's critique of formalism in economics and his case for a more institutional economics based upon a reconstitution of the facts of economic life on as wide an historical basis as possible. The argument below reviews Polanyi's argument with regard to the relation between economic anthropology and comparative economics, the contrast between the formalist and substantive approaches to economic analysis, the notion of an economistic fallacy, the most important limitations of the conventional formalist economics approach, and the nature and import of the new departure that Polanyi envisioned. James Ronald Stanfield, Michael C. Carroll, Mary V. Wrenn (2006), Karl Polanyi on the Limitations of Formalism in Economics, in Donald C. Wood (ed.) Choice in Economic Contexts (Research in Economic Anthropology, Volume 25) Emerald Group Publishing Limited, pp.241 - 266
Economics; Anthropology
Keywords: economic anthropology; formalism

Editor's Letter - Lomnitz, Claudio (Public Culture, 2006)
This article previews this edition of "Public Culture" and focuses on Karl Polanyi's theories on capitalism. Polanyi believed in trade liberalization and felt that market regulation is the principal obstacle to collective prosperity. He thought that unregulated markets could bring an end to poverty, and would resolve the chronic dislocation, inequality, and vulnerability that have marked capitalism from its inception. Polanyi demonstrated that market liberalization was only achieved through concerted state intervention.
Anthropology
Keywords: capitalism; free trade; intervention (federal government); poverty; public culture (periodical)